Biochemical changes induced by Phytophthora colocasiae infection in taro (Colocasia esculenta) - SUGHAI, S K; GURUN, KUSUM (The Indian Journal of Agricultural Sciences, 2011)
Progressive growth of blight lesions and increase in disease severity levels resulted and corresponding reduction in carbohydrate, protein and oxalate contents of leaf. Partly rotten eanns also showed significant reduction in these quality paranleters.